2 μm Laser generation and amplification based on dual Tm3+-doped high-Q silica microsphere using an ASE light source for pumping. (September 2022) - Huang, YanTang; Xu, Qiling; Peng, Senlin; Xu, CanHua; Liao, TingDi
Highlights: A kind of whispering gallery mode laser amplifier was proposed. The amplification factor β is 11.12 dB for 2 μm WGM laser. A C-band amplified spontaneous emission (ASE) light source was employed to excite the different diameters of Tm 3+ -doped silica microspheres simultaneously, and resisting the interference of vibration and temperature variations. Six photons up-conversion fluorescence could also be observed as the C-band ASE light pumped the TDSM. Abstract: A dual Tm 3+ -doped silica microsphere-tapered optical fiber (TDSM-TOF) structure was proposed to excite 2 μm whispering gallery mode (WGM) laser generation and amplification. A C-band amplified spontaneous emission (ASE) light source was employed as the pumping source of TDSMs. The absorption spectra and the laser spectra of TDSM1 and TDSM2 and their concatenations were measured respectively. The ASE source has polarized light in any direction to satisfy the resonance of the microsphere cavity, the laser longitudinal mode distributions can counteract the influence of polarization variation because of environmental vibration. Meanwhile, six photons up-conversion fluorescence could also be observed.